1990
DOI: 10.1007/bf01914056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iron ion additions on the thermal decomposition of basic zinc carbonate

Abstract: Thermal decomposition of pure basic zinc carbonate (BZC) and doped or mixed with iron ions were studied using TG, DTA and kinetics of isothermal decomposition. The TG and DTA investigations revealed that, the presence of iron ions retards the decomposition processes of (BZC). Also, the retardation effect increases on increasing of iron concentration up to 50 at.%. The curves of isothermal decomposition show the usual sigmoidal character. The decomposition velocity eontsant (K) values are plotted vs. liT accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…However, the observed weight loss was 23.3% (0.43% relative standard deviation), suggesting that nonvolatile impurities may be present in the test lot. In addition, the temperature of maximum weight loss (approximately 270 °C) in our investigation was slightly greater than that observed in similar studies (Said et al 1990), thus supporting the presence of non-volatile impurities. When these data are taken collectively with XRD observations, ZnO is a plausible minor component of the test lot of zinc carbonate basic.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…However, the observed weight loss was 23.3% (0.43% relative standard deviation), suggesting that nonvolatile impurities may be present in the test lot. In addition, the temperature of maximum weight loss (approximately 270 °C) in our investigation was slightly greater than that observed in similar studies (Said et al 1990), thus supporting the presence of non-volatile impurities. When these data are taken collectively with XRD observations, ZnO is a plausible minor component of the test lot of zinc carbonate basic.…”
Section: Resultssupporting
confidence: 69%
“…These compounds have a variety of industrial applications and have been used as drilling fluid additives (Cameron 2005), used in respirators (Okutani et al. 1993, Zhang, Fortier, and Dahn 2004), and as synthetic precursors for reactive metal oxide fine particles (Said et al 1990, Koga and Tanaka 2005) for use in solar cells, cosmetic products, gas sensors, paints, pigments, and a variety of other products (Kanari et al 2004, Feng et al 2005, Cao et al 2009, Du, Liu, and Chen 2009, Zhang et al 2009, Anžlovar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The initial decomposition product was identified as Na 2 SiO 3 , irrespective of the mixing ratio of Na 2 CO 3 /SiO 2 . Said et al studied the influence of iron additions on the thermal decomposition of zinc carbonate . They observed that the presence of iron retarded the decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrates receive a lot a attention (99,100). Typical of the work on carbonates is the study showing the dependence of decomposition upon the pressure of C02 for Ag2C03 (101) and the influence of ionic additions to the decomposition of ZnC03 (102). In molten potassium pyrosulfate, the reactions of six metal nitrates were investigated by thermal analysis (103).…”
Section: Inorganic Compoundsmentioning
confidence: 99%